Parallel Data Acquisition and Processing with Paspberry Pi Clusters - Agonás, A.; Szemes, Péter Tamás (International Journal of Engineering and Management Sciences, 2017)
Computer network was built from Raspberry Pis, what can solve research task in the filed of building mechatronics. According to the results, it can state the cluster built from Raspberry Pis, can process indoor sensor data effectively